Deep mitochondrial introgression and hybridization among ecologically divergent vole species - Bastos-Silveira, Cristiane (2020)
The completion of speciation is typically difﬁcult to ascertain in rapidly diverging taxa but the amount of hybridization and gene ﬂow in sympatry or parapatry contains important information about the level of reproductive isolation achieved. Here, we examined the progress in speciation between the Mediterranean (Microtus duodecimco- status) and the Lusitanian pine vole (M. lusitanicus), which are part of the most rapid radiation of species known in mammals. These two Iberian pine voles are classiﬁed as separate species because of differences in morphology and ecology, but relatively many ambiguous individuals can be found in sympatric conditions. Our phylogenetic analyses of rangewide data from the mitochondrial cytochrome b gene (mtDNA) dem- onstrated high levels of diversity and a basal separation in two parapatric lineages. However, mtDNA afﬁliation was at odds with morphological classiﬁcation or geo- graphical distribution of the taxa. In contrast, statistical analyses of microsatellites (nucDNA) showed two clear genetic clusters in allopatry and sympatry generally matching morphological classiﬁcation. This cytonuclear discordance over a large geo- graphic area suggests historical introgression of mtDNA from M. duodecimcostatus to M. lusitanicus. There was statistical evidence for at least two recent hybrids in the sympatry zone but gene ﬂow is apparently low given clear-cut differences in nucDNA. Our results indicate a relatively advanced speciation process in these Iberian pine voles without fully established reproductive isolation. This situation enables use of combined population genomic and experimental approaches for the separation of pat- terns and mechanisms in the ongoing explosive diversiﬁcation of these and other Arvicoline rodents in the future.